South Kincumber Cemetery inscriptions & index - Bakewell, Sharon; Bakewell, Kerrie; Central Coast Family History Group (N.S.W.) ([Gosford, N.S.W.] : Gosford City Council, 1992)
For use in family history research.
Cover title: South Kincumber inscriptions and index.
Keywords: Holy Cross Church (Kincumber, N.S.W.); Registers of births, etc. -- New South Wales -- Kincumber; Cemeteries -- New South Wales -- Kincumber; Epitaphs -- New South Wales -- Kincumber